The Effect of The STEM Approach on Students’ Critical Thinking Skills in Grade-11 SMAN 9 Makassar - Salam, Nurafni; Saleh, Andi Rahmat; Faisal, Faisal (Universitas Negeri Makassar, 2025)
Abstract. This study investigates the effect of the STEM (Science, Technology, Engineering, and Mathematics) approach on the critical thinking skills of 11th-grade students at SMA Negeri 9 Makassar. The research was conducted at SMA Negeri 9 Makassar. The population comprised all 11th-grade students, divided into two classes. Sample selection was based on the average final exam scores, resulting in XI Biology 2 being assigned as the experimental class and XI Biology 4 as the control class. Research instruments included an observation sheet for STEM-based practical activities and an essay test to measure critical thinking skills. Data were analyzed using descriptive statistics and inferential statistics with the SPSS program. The results indicate that the implementation of the STEM approach positively influences students’ critical thinking skills. This is evidenced by the higher average critical thinking score of the experimental class (79.61) compared to the control class (65.10). Therefore, the STEM approach can be concluded to have a significant impact on enhancing students’ critical thinking skills.Keywords: STEM, biology, critical thinking, student